Occupational Health Problems and Lifestyle Changes Among Novice Working-From-Home Workers Amid the COVID-19 Pandemic - Ekpanyaskul, Chatchai; Padungtod, Chantana (Safety and health at work, 2021)
Social distancing by working-from-home is an effective measure to decrease the spread of COVID-19. However, this new work pattern could also affect the well-being of workers. Therefore, the aim of the study was to study the magnitude of occupational health problems and lifestyle changes among workers who have only recently started working from home. A cross-sectional study was conducted using online self-administered questionnaires during the coronavirus disease 2019 pandemic in the Bangkok metropolitan area, Thailand. The participants were from any organization that allowed working from home. The demographic data including the analysis of the characteristics of working from home, the occurrence of occupational health problems, and the lifestyle changes caused by working from home were analyzed. A total of 869 workers were included as study participants. The highest prevalence of physical health problems among all workers was identified to be weight gain at a rate of 40.97% (95% confidence interval = 37.69–44.24), and the highest prevalence of psychosocial problems was identified to be cabin fever at a rate of 31.28% (95% confidence interval = 26.66–35.90%) among full-time working-from-home workers. The health effects that were significantly related to the intensity of working from home (p for trends <0.05), either positively or negatively, included body weight changes, ergonomic problems, indoor environmental problems, and psychosocial problems. Meanwhile, the lifestyle changes related to work intensity included eating pattern, sleep habits, and exercise. Working from home can affect workers' well-being in various aspects. Hence, occupational health providers must prepare for risk prevention and health promotion in this “new normal” working life pattern and for future pandemics.